The Role of Microteaching in Increasing Self-Confidence of UMMY Economic Education Students - Dinda Ramadhani; Desi Armi Eka Putri (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Based on the articles collected and analyzed, it can be concluded that the role of microteaching in increasing self-confidence is very important. Because with microteaching learning, students can hone their skills so that they can increase their confidence when teaching or when going to school. Then students can build self-confidence in practicing speaking skills to become more competent teachers before going into the field.